Cell mediated immune responses following revaccination with an influenza A/H5N1 vaccine. Issue 4 (20th January 2016) - Mbawuike, Innocent N.; Atmar, Robert L.; Patel, Shital M.; Corry, David B.; Winokur, Patricia L.; Brady, Rebecca C.; Chen, Wilbur H.; Edwards, Kathryn M.; Creech, C. Buddy; Walter, Emmanuel B.; Frey, Sharon E.; Belshe, Robert B.; et al.
Highlights: CMI responses occurred following administration of an inactivated A/H5N1 vaccine. High dose vaccine increased the magnitude of CMI response only in the unprimed subjects. IFN-γ nSFC levels correlated with IFN-γ concentrations in PBMC supernatants. Abstract: Purpose: The study aims were to determine whether inactivated influenza A/H5N1 vaccine administration elicited cell mediated immune (CMI) responses and the impact of adjuvant, vaccine dose and subject age on these responses. Methods: Adults who were previously primed with either adjuvanted or unadjuvanted, inactivated, A/H5N1/Vietnam/1203/2004 (Clade 1) vaccine or unprimed (received placebo) in previous vaccine studies were randomized to receive one (primed) or two (unprimed) 15- or 90-mcg doses of inactivated, A/H5N1/Indonesia/05/05 (Clade 2) vaccine. Peripheral blood mononuclear cells (PBMCs) were collected and analyzed from a subset of vaccinees to assess CMI responses using IFN-γ and granzyme B ELISPOT assays. Cytokine measurements were performed on PBMC supernatants after stimulation with H5N1 virus. Results: PBMCs were available from 177 participants; 88 and 89 received 15-mcg and 90-mcg of unadjuvanted clade 2 vaccine, respectively. Following H5N1 clade 1 stimulation, IFN-γ but not granzyme B normalized spot-forming cell numbers had statistically significant increased numbers at each of the post-vaccination timepoints compared to baseline in pooled analyses of all vaccine doses and age groups. Clade 2 stimulation resulted in statistically significant increased numbers of IFN-γ cells only 180 days following the last vaccination. Responses were similar among younger and older study participants, as were responses among those primed with alum-adjuvanted or non-adjuvanted clade 1 H5N1 vaccines. The dosage of clade 2 vaccine did not impact CMI responses among primed subjects, but responses were statistically significantly greater in unprimed recipients of the 90-mcg dosage compared to unprimed recipients of the 15-mcg dosage. IFN-γ levels in the supernatants of stimulated PBMC were strongly correlated with IFN-γ ELISPOT results. Conclusion: CMI responses occur in adults administered influenza A/H5N1 inactivated influenza vaccine.